دراسة استبيانية حول نباتي السدر والقراص الطبيين المستعملين لعلاج الحساسية والالتهابات الجلدية لمنطقة الوادي - الجزائر- - تواتي ايمان; قديري نائلة (University of eloued . جامعة الوادي, 2025)
Our study aims to document local knowledge related to the use of medicinal plants in the treatment of skin inflammations and skin allergies in the El Oued region, in light of the lack of sufficient scientific studies on the effectiveness of these plants and their methods of use. The study sought to identify the most commonly used plant species, the parts of the plants employed, and the common methods of preparation and application among the local population. This study focused on two main components: • The theoretical part explored the basic concepts of skin inflammations and allergies, in addition to a theoretical review of Ziziphus spina-christi (jujube) and Urtica dioica L (nettle), which are well known for their therapeutic properties, along with previous studies on their medicinal applications. • The practical part involved conducting a field survey that included direct interviews with herbalists to collect data on the types of plants used in the treatment of skin allergies and inflammations. From this study, we identified a wide range of medicinal plants used by people in the El Oued region to treat skin allergies and inflammations. We selected the two most frequently cited plants: • Ziziphus spina-christi (jujube) • Urtica dioica L. (nettle) Based on this, we developed a questionnaire on the use of these plants and distributed 100 copies across various population groups. The study spanned two months, during which the results revealed a rich body of traditional knowledge that has been orally transmitted across generations, along with a strong reliance on certain plants known for their traditional effectiveness.
التنوع الحيوي وفيزيولوجيا النبات
Keywords: skin allergies and inflammations; herbs; El Oued; nettle (Urtica dioica); jujube (Ziziphus spina-christi).